Evaluation of ethnobotanically selected Benin medicinal plants for their in vitro antiplasmodial activity - WENIGER, Bernard; LAGNIKA, LATIFOU (My University, 2004)
Twenty extracts from nine Benin medicinal plants, traditionally used to treat malaria, were screened for in vitro antiplasmodial activity towards Plasmodium falciparum K1 chloroquine resistant and 3D7 chloroquine sensitive strains. All plants showed antiplasmodial activity below 10g/ml. Nine extracts exhibited IC50 values below 5g/ml towards one or both of the two strains. The most active extract towards the sensitive 3D7 strain was the methanolic extract of Croton lobatus aerial part, with an IC50 value of 0.38g/ml. The best inhibition of the growth of Plasmodium falciparum resistant K1 strain was observed with the methylene chloride extract of Hybanthus enneaspermus and with the methanolic extract of Croton lobatus roots (IC50 = 2.57 and 2.80g/ml, respectively).
Keywords: Malaria; Traditional medicine; Benin